Advances in Orthopedic Trauma - Wiria Aryanta (HM Publisher, 2016)
Orthopedic trauma is a broad term describing all kinds of injuries affecting the bones, joints, muscles, tendons, and ligaments in any part of the body that are caused by trauma. The term is wide - ranging and may refer to minor fractures or severely broken bones with a direct threat to the patient’s life. Orthopaedic surgeries focused on treating fractured bones and making sure the injured part of the body regains its original strength and maximum function it used to have prior to the injury.